Polemik Nasakh dalam Kajian Ilmu Al-Qur’an - Fawaid, Ahmad (SUHUF, 2011)
This article explores an important discipline in Qur’anic sciences, namely nasikh-mansukh (the abrogator and the abrogated), referring to the abrogation of certain Qur’anic verses. Although Muslim scholars are in dispute over the exact meaning and implications of the meaning of abrogation (naskh) in the Qur’an, nevertheless there are some points of agreement. Neither ide either completely rejects the concept of abrogation, or vice versa, and their differences are not non-negotiable. In some cases, the two sides will arrive at the same conclusion in that they will both admit the existence of the concept of naskh (abrogation) in the Qur’an, but will disagree on its meaning. One side will interpret naskh as complete cancellation and erasure, while the other side tends to interpret it as implying a delay in the implementation (or rather, evolution) of Islamic law (shari‘ah). Thus one side admits of intra-Qur'anic abrogation, while the other only admits of abrogation in extra-Qur'anic contexts.